Characteristics and One Year Survival of Mediastinal Germ Cell and Its Influencing Factors - Elisna Syahruddin; Mia Elhidsi; Erni Mudhiati; Jamal Zaini (Jurnal Respirologi Indonesia, 2020)
Backgorunds: Mediastinal germ cell tumors are relatively rare. These tumors can be benign or malignant, which has a poor prognosis malignant. Nowadays, multimodality therapy can improve the survival rate of patients’ mediastinal germ cell tumors. This study aims to determine the characteristics and factors affecting the 1-year survival rate of mediastinal germ cell tumors patients in the Persahabatan Hospital, Jakarta. Methods: The study was conducted using retrospective cohort of mediastinal germ cell tumors patients medical records in Persahabatan Hospital, Jakarta from January 1, 2007 to December 31, 2012. Data obtained were analyzed using Kaplan Meier analysis of survival. Results: As much as 60 subjects participated in this study. Mediastinal germ cell tumors were found more in male (80%) with a median age of 21 years and especially in the age group of 20-29 years (43.3%). Most clinical symptoms found were shortness of breath (66.7%), most patients came with performance status (PS) 2 (50%). The majority of the mediastinal germ cell tumors found were teratomas (53.3%), followed with nonseminoma (40%) and seminomas (6.7%). Factors affecting the survival rate of mediastinal germ cell tumors were performance status of, the patients, treatment, complications and location of the tumors. One-year survival rate of mediastinal germ cell tumors in this study was 41.67% and affected by patients’ performance status, tumor location, complications and treatment. Conclusion: Mediastinal germ cell tumors were mostly found in male, with the chief complain of dypnea and mostly was teratoma. Mediastinal germ cell tumors have high mortality rate. The 1-year survival was influenced by patient’s performance status, tumor location, complications and treatment. (J Respir Indo. 2020; 40(2): 97-102)